Ultrasound imaging in urogynecology – state of the art 2016 - Bogusiewicz, Michał (Menopause Review/Przegląd Menopauzalny, 2016)
The role of ultrasound imaging in urogynecology is not clearly defined. Despite significant developments in visualization techniques and interpretation of images, pelvic ultrasound is still more a tool for research than for clinical practice. Structures of the lower genitourinary tract and pelvic floor can be visualized from different approaches: transperineal, introital, transvaginal, abdominal or endoanal. According to contemporary guidelines and recommendations, the role of ultrasound in urogynecology is limited to the measurement of post-void residue. However, in many instances, including planning and audit of surgical procedures, management of recurrences or complications, ultrasound may be proposed as the initial examination of choice. Ultrasound may be used for assessment of bladder neck mobility before anti-incontinence procedures. On rare occasions it is helpful in recognition of pathologies mimicking vaginal prolapse such as vaginal cyst, urethral diverticula or rectal intussusception. In patients subjected to suburethral slings, causes of surgery failure or postsurgical voiding dysfunctions can be revealed by imaging. Many reports link the location of a tape close to the bladder neck to unfavorable outcomes of sling surgery. Some postoperative complications, such as urinary retention, mesh malposition, hematoma, or urinary tract injury, can be diagnosed by ultrasound. On the other hand, the clinical value of some applications of ultrasound in urogynecology, for example measurement of the bladder wall thickness as a marker of detrusor overactivity, has not been proved.